ORIGEM E INSTITUCIONALIZAÇÃO DA IGREJA METODISTA WESLEYANA - Santos, Valter Borges dos (2014)
This text is the result of an undertaken research about the Wesleyan Methodist Church historical origin and its features, a pentecostal dissident of the Brazils Methodist Church, started in Rio de Janeiro, in the late 1960s. Aimed with this investigation, analyze the intrafield reasons and religious extra field that stimulated that happening. We emphasize the shepherd, administrative and theological conflicts which made of the Brazils Methodist Church First Ecclesiastical Region a battle field where shepherds, lay and bishop involved themselves in fights that generated this split. The sources of this split are, in our point of view, in the lack of the historical protestantism adequacy to the country s social, economic and cultural conditions. Different from pentecostalism that found a bigger identification with Brazilians culture, the protestantism, including methodist, which were not able to gain the poor layers, getting to the middle class. So then the appearance of pentecostalization process in many Brazilian denominations between the presbyterians, the baptists, congregational, lutherans, methodists and others. The Wesleyan Methodist Church has emerged institutionalized, following the models of the Methodist Church of Brazil, where the group left. Then she was taking a Pentecostal identity perpetuating the religious field by creating their own institutional and bureaucratic mechanisms.